High Electric Production by Membraneless Microbial Fuel Cell with Up Flow Operation Using Acetate Wastewater - Aris Mukimin; Nur Zen; Hanny Vistanty; Purwanto Agus (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2020)
Microbial fuel cell (MFC) is a new proposed technology reported to generate renewable energy while simultaneously treating wastewater. Membraneless microbial fuel cell (ML-MFC) system was developed to eliminate the requirement of membrane which is expensive and prone to clogging while enhancing electricity generation and wastewater treatment efficiency. For this purpose, a reactor was designed in two chambers and connected via three pipes (1 cm in diameter) to enhance fluid diffusion. Influent flowrate was maintained by adjusting peristaltic pump at the base of anaerobic chamber. Carbon cloth (235 cm2) was used as anode and paired with gas diffusion layer (GDL) carbon-Pt as cathode. Anaerobic sludge was filtered and used as starter feed for the anaerobic chamber. The experiment was carried out by feeding synthetic wastewater to anaerobic chamber; while current response and potential were recorded. Performance of reactor was evaluated in terms of chemical oxygen demand (COD). Electroactive microbe was inoculated from anaerobic sludge and showed current response (0.55-0.65 mA) at 0,35 V, range of diameter 1.5-2 µm. The result of microscopics can showed three different species. The microbial performance was increased by adding ferric oxide 1 mM addition as acceptor electron. The reactor was able to generate current, voltage, and electricity power of 0.36 mA, 110 mV, and 40 mWatt (1.5 Watt/m2), respectively, while reaching COD removal and maximum coulomb efficiency (EC) of 16% and 10.18%, respectively.